GROWTH OF PURPLE CABBAGE (Brassica oleracea L. var. capitate f. rubra) ON THE ADMINISTRATION OF POLYETHYLENE GLYCOL 6000 (PEG 6000) - Chandra Aria Wicaksono; Tundjung Tripeni Handayani; Martha Lulus Lande; Zulkifli Zulkifli (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2021)
Purple cabbage plants require an adequate supply of water in the process of growing. So that if there is a lack of water it can result in stressful conditions then the growth of purple cabbage is disrupted and can even cause death. The purpose of this study was to determine the tolerance limits of purple cabbage to PEG 6000, and to determine the effect of PEG 6000 on the growth of purple cabbage as a simulation of drought stress. This research was conducted using a completely randomized design with the main factor being PEG 6000 with 5 concentration levels: 0 % w/v, 10% w/v, 20% w/v, 30% w/v and 40% w/v with 5 replications. As parameters are plant height, length, width, and number of leaves, also chlorophyll content. Then analyzed with the Levene test, one way ANOVA and the Tukey HSD test at 5% level. Based on the results of the research, it can be concluded that giving PEG 6000 shows that the tolerance limit for purple cabbage plants to PEG 6000 treatment is at a concentration of 10%, then giving PEG 6000 gives a negative response to the growth of purple cabbage which is indicated by a decrease in plant height, leaf length, leaf width, number of leaf, also chlorophyll a, b, and total chlorophyll content.